Improving Student Learning Outcomes Through IT-Based Discovery Learning Class III Elementary School Suggestion Sentence Material - Rosiana, Eva Zumroh (Universitas Sebelas Maret, 2020)
This classroom action research aims to improve student learning outcomes for suggestion sentences by implementing an IT-based discovery learning model in class III SD Negeri Mrisen 1, Wonosalam District, Demak Regency, for the 2019/2020 school year. The subjects in this study were third grade students of SD Negeri Mrisen 1 which consisted of 19 students. This research consists of 3 cycles. The instruments used in data collection were observation sheets and formative lesspaper tests in the form of google form. This can be evidenced by the increase in the achievement of students' formative test scores in the first cycle (59.47%), an increase of 74.21% in the second cycle and again to 85.79% in the third cycle. This shows that the application of the IT-based discovery learning learning model at SD Negeri Mrisen 1 can increase the learning outcomes of third grade students by 26.32% from cycle I to cycle III.